140k views
3 votes
Can you help explain how to solve this for me?

Can you help explain how to solve this for me?-example-1

1 Answer

4 votes

SOLUTION:


d=√((y_2-y_1)^2+(x_2-x_1)^2)
\begin{gathered} d=√((-4-8)^2+(5--6)^2) \\ d=√(-12^2+11^2) \\ d=√(265)=16.28 \end{gathered}

b.


\begin{gathered} m=(x_2+x_1)/(2),(y_2+y_1)/(2) \\ m=((-6+5)/(2),(-4+8)/(2)) \\ m=(-(1)/(2),2) \end{gathered}

User ZhouW
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.